Answer:
To evaluate the given expressions, we need to follow the order of operations, also known as PEMDAS (Parentheses, Exponents, Multiplication and Division from left to right, Addition and Subtraction from left to right). Let's simplify each expression step by step:
1. 8 + 6:
The addition operation is straightforward. Adding 8 and 6 gives us the answer of 14.
2. 12 - 2.6:
Again, we perform the subtraction operation. Subtracting 2.6 from 12 gives us the answer of 9.4.
3. 28 + 7.4:
Similar to the first expression, we add 28 and 7.4 to get the answer of 35.4.
Therefore, the simplified expressions are as follows:
- 8 + 6 = 14
- 12 - 2.6 = 9.4
- 28 + 7.4 = 35.4
Step-by-step explanation:
The ladder leaning against the wall forms a right angled triangle with the gound and the wall. So we can use the formula:
a² + b² = c²
The ladder is the hypotenuse c²
The vertical leg is b²
The base or horizontal leg is a²
We need to find the length of the base a², so:
a² = c² - b²
a² = 5² - 4²
a² = 25 - 16
a² = 9
a = √9
a = 3
Therefore the bottom of the ladder must be 3 feet from the wall.
The graph of an equation is the set of all points that are solutions of the equation. Frequently, a relationship between two quantities can be expressed as an equation in two variables. For instance, we can write the equation of our problem as the following form:
So, by graphing we want to know the x-intercepts. This graph is illustrated in the Figure below. As you can see, points in red are the solution to this problem that are the x-intercepts of our previously defined function . These points are:
The solutions of the given quadratic equation are x=-3 and x=1.
The given quadratic equation is x²+2x-3=0.
By using splitting middle term method, the given equation can be solved as follows:
Here, x²+3x-x-3=0
x(x+3)-1(x+3)=0
(x+3)(x-1)=0
x+3=0 and x-1=0
x=-3 and x=1
Therefore, the solutions of the given quadratic equation are x=-3 and x=1.
To learn more about the solution of quadratic equation visit:
brainly.com/question/18305483.
#SPJ6
6:10
b
9:12
c
10:40
d
8:6
Answer:
⅓w³
Step-by-step explanation:
What the answer super easy points
Answer:
7/8
Step-by-step explanation:
convert 1/2 to 4/8 and add to 3/8
Answer:
1/2 + 3/8 = 7/8
Step-by-step explanation:
i hope this helps you! :)
Answer:
Inverse proportion
Step-by-step explanation:
Inverse proportion, as x increases, y decreases